Security Threats and Possible Countermeasures in Applications Covering Different Industry Domains - Samaila, Musa Gwani (2020)
The world is witnessing the emerging role of Internet of Things (IoT) as a technology that is transforming different industries, global community and its economy. Currently, a plethora of interconnected smart devices have been deployed for diverse pervasive applications and services, and billions more are expected to be connected to the Internet in the near future. The potential benefits of IoT include improved quality of life, convenience, enhanced energy efficiency, and more productivity. Alongside these potential benefits, however, come increased security risks and potential for abuse. Arguably, this is partly because many IoT start-ups and electronics hobbyists lack security expertise, and some established companies do not make security a priority in their designs, and hence they produce IoT devices that are often ill-equipped in terms of security. In this paper, we discuss different IoT application areas, and identify security threats in IoT architecture. We consider security requirements and present typical security threats for each of the application domains. Finally, we present several possible security countermeasures, and introduce the IoT Hardware Platform Security Advisor (IoT-HarPSecA) framework, which is still under development. IoT-HarPSecA is aimed at facilitating the design and prototyping of secure IoT devices.